PENGARUH KESADARAN PERPAJAKAN DAN KEMUDAHAN PENGGUNAAN E-FILING TERHADAP KEPATUHAN PELAPORAN WPOP DI KPP PRATAMA BATAM SELATAN - Madinah, Indah Utami Nur; Br. Purba, Neni Marlina (LPPM Universitas Putera Batam, 2021)
The purpose of this study was to to analyze and determine the effect of tax awareness and ease of use of e-filing on WPOP reporting compliance at KPP Pratama Batam Selatan. This research consists of three variables, namely tax awareness and ease of use of e-filing as an independent variable and compliance with individual taxpayer reporting as the dependent variable. This study uses primary data obtained from questionnaires distributed to individual taxpayers who are registered at KPP Pratama Batam Selatan via google form. The population of this study was 319.154 respondents. The sampling technique used simple random sampling using the Slovin formula, so that the sample obtained was 100 respondents. The data analysis techniques used in this study were validity and reliability tests, descriptive statistical analysis, normality test, multicollinearity test and heteroscedasticity test, multiple linear regression test and T test, F test and determination analysis.This study uses the SPSS version 25 program. The results of this study indicate that tax awareness has a positive and significant effect on reporting compliance of individual taxpayers at KPP Pratama Batam Selatan, the ease of using e-filing has a positive and significant effect on reporting compliance of individual taxpayers at KPP Pratama Batam Selatan.